2017
DOI: 10.7753/ijsea0603.1003
|View full text |Cite
|
Sign up to set email alerts
|

New Physiologically Active Kaempferol Glucoside from Abutilon pannosum

Abstract: Abstract:The phytochemical investigation of Abutilon pannosum (Malvaceae) collected from arable land of Tennidah village, Dakhla Oasis, Western Desert, Egypt, resulted in the separation and identification of a new flavonoid, kaempferol 4'-O-(6"-O-E-p-coumaroyl)-β-Dglucopyranoside 1 from butanol fraction, in addition to the identification of the volatile constituents of petroleum ether and methylene chloride by GC/MS analysis. Structure of the separated compound was elucidated by spectral analysis. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The antimicrobial activity indexes of methanol extract, methyle chloride extract and petroleum ether extracts of A. pannosum leaves against Escherichia coli were found to be 66.7%, 33.3%, and 0.0%, respectively, while the activity indexes of methylene chloride, methanol and petroleum ether extracts against Staphylococcus aureus were 63.6%, 59.1% and 9.1%, respectively, and against Candida albicans, their activity indexes were 38.5%, 34.6%, and 11.5%, respectively (Kamel et al, 2017). Saini et al (2014) found that the alcoholic leaf extract of A. indicum had a positive and good response against the fungi Microsporum gypseum and Penicelliium chrysogenum, whereas the aqueous leaf extract showed no activity against the fungi under study.…”
Section: Antimicrobial Activity Of a Pannosum Leaf Extractmentioning
confidence: 97%
See 2 more Smart Citations
“…The antimicrobial activity indexes of methanol extract, methyle chloride extract and petroleum ether extracts of A. pannosum leaves against Escherichia coli were found to be 66.7%, 33.3%, and 0.0%, respectively, while the activity indexes of methylene chloride, methanol and petroleum ether extracts against Staphylococcus aureus were 63.6%, 59.1% and 9.1%, respectively, and against Candida albicans, their activity indexes were 38.5%, 34.6%, and 11.5%, respectively (Kamel et al, 2017). Saini et al (2014) found that the alcoholic leaf extract of A. indicum had a positive and good response against the fungi Microsporum gypseum and Penicelliium chrysogenum, whereas the aqueous leaf extract showed no activity against the fungi under study.…”
Section: Antimicrobial Activity Of a Pannosum Leaf Extractmentioning
confidence: 97%
“…pannosum, 11,14,17-eicosatrienoic acid (21.05%), 9,12,15-octadecatrien-1-ol (21.03%), 9,12,15-octadecenoic acid (21.01%), pentadecanoic acid (16.81%), citronellylvalerate (11.08%), 9-eicosyne (11.06%), phytol (11.04%), neophytadiene (11.02%), α-tocopherol (4.48%), n-hexadecanoic acid (2.16%), squalene (2.75%) were identified (Aadesariya et al, 2018). In the petroleum ether extract, 31 compounds were identified, with n-nonadecane (8.28%), n-eicosane (7.63%), n-octadecane (7.31 percent), n-heptadecane (7.29%), and n-hexadecane (6.54 percent) as the major components, while in the methylene chloride extract, 29 compounds were identified, with phytol (31.69%), squalene (15.76%), neophytadiene (5.58%), and n-hexadecanoic acid (4.97%) as the major components (Kamel et al, 2017). Triterpenes, fatty acids, monoterpenes, aromatic flavoring agents, esters, n-alkanes, saturated aliphatic hydrocarbons, diterpenes, olefins, monoglycerides, monoterpenoid phenols, poly unsaturated poly acids, and Vitamin E were found in the acetonitrile leaf extract of A.pannosum by GC/MS analysis (Sejalsadhu et al, 2016).…”
Section: Chemical Composition Of a Pannosum Leaf Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the available literature for the three species; (A. pannosum, A. hybridum and A. hirtum) no data was reported for their lipoidal matter content, thus in our previous report 10 a comparative study of their lipoidal content of their aerial parts was done. Also, there are no data could be traced concerning the constituents of Abutilon hybridum, on the other hand, apigenin 7-Oβ-D (6 \\ -p-coumaroyl) glucopyranoside 6 , apigenin 7-O--D-6 \\ -p-hydroxycinnamoyl glucopyranoside and kaempferol 4′-O-(6 \\ -O-E-p-coumaroyl)-β-Dglucopyranoside were identified from Abutilon pannosum [11][12] and one study could be traced concerning the flavonoids and phenolic acids of the aerial parts of Abutilon hirtum showed the presence of kaempferol, quercetin, rutin, gallic, p-coumaric and caffeic acids 13 . Basing on these data, the present study was aimed to analyze the phenolic compounds present in the aerial parts of three Abutilon species (A. pannosum, A. hybridum and A. hirtum) using HPLC technique.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant activities of various extracts of A. pannosum during in vitro assays were reported (Aadesariya, Ram, & Dave, ). In addition, antimicrobial, cytotoxic and antioxidant activities of A. pannosum were also studied (Kamel, Elfadawy, Elshamy, & Abdel‐Moghib, ). In this investigation, we have evaluated the presence of various phytochemical classes and the aphrodisiac potential of the methanol extract of A. pannosum in male rat.…”
Section: Introductionmentioning
confidence: 99%